Medical Gastronomy and Glucofriendly Gastronomy: Tools for Chronic Disease and Diabetes Care - Sanjay Kalra; Atul Dhingra; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
In this communication, we introduce and describe the concepts of medical gastronomy, glucofriendly gastronomy, and gastronomic phenotypes. We discuss the clinical relevance of these frameworks in chronic disease management, including obesity and diabetes care. We propose the use of the phrase ‘medical gastronomy’ to describe the practice of choosing, cooking and consuming food, which is not only appealing or tasty, but nutritious and healthy as well. ‘Glucofriendly gastronomy’ conceptualizes the art and science of choosing, cooking and consuming food, which is not only safe for persons living with diabetes, but appealing and tasty, too. The term ‘gastronomic phenotype’ is the sum of all attributes related to the practice or art of choosing, cooking and consuming food. This includes the individual’s likes (dislikes), preferences and choices related to meal frequency, meal composition, meal quantity and meal sequencing. Keywords: Culinary medicine, diabetes, diet, nutrition, obesity, person centred care